(untitled) (The Review of Diabetic Studies, 2024)
Liver transplantation is a critical intervention for patients with end-stage liver disease, necessitating a comprehensive and coordinated approach to care. The success of this complex procedure relies not only on the surgical expertise of the transplant team but also on the integral contributions of a multidisciplinary team, with nursing playing a pivotal role. This review explores the multifaceted responsibilities of nurses in the care of liver transplant patients, emphasizing their roles as advocates, educators, and caregivers throughout the transplant process.In the pre-operative phase, nurses conduct thorough assessments to evaluate patients’ physical and psychological readiness for surgery, while also providing essential education about the transplant process and addressing any barriers to care. Their involvement is crucial in fostering patient understanding and compliance, which are vital for optimizing outcomes. During the intra-operative phase, nurses ensure patient safety and comfort, closely monitoring vital signs and assisting the surgical team in maintaining a sterile environment. Their vigilance and expertise are essential in recognizing and responding to any changes in the patient’s condition.Post- operatively, nurses play a critical role in monitoring for complications, managing pain, and providing education on medication adherence and lifestyle modifications necessary for the health of the transplanted liver. They also facilitate ongoing follow-up care, coordinating with other members of the multidisciplinary team to ensure comprehensive management of the patient’s health.This review highlights the essential contributions of nursing in each phase of liver transplantation, underscoring the importance of a collaborative, multidisciplinary approach to patient care. By recognizing and enhancing the role of nursing, healthcare systems can improve patient outcomes and quality of life for liver transplant recipients. Ultimately, this comprehensive review aims to inform best practices and promote the integration of nursing into the multidisciplinary framework of liver transplantation, ensuring that patients receive holistic and effective care throughout their transplant journey.